Brand mergers: examining consumers' responses to name and logo design - César - Machado, Joana (2013)
Abstract Purpose – In the context of a merger, the management of corporate identity – in particular of corporate names and logos – assumes a critical role. This paper aims to explore how name and logo design characteristics, and specifically figurativeness, influence consumer preferences in the context of a brand merger, in the banking sector. Design/methodology/approach – This study develops a typology of the alternative corporate identity structures that may be assumed in the context of a brand merger by drawing on a literature review and secondary data, as well as an exploratory study analyzing consumers’ preferences regarding alternative branding strategies. Findings – The results suggest that there is a clear preference for figurative logos. Furthermore, there is evidence that logos may be as important as the company name in a merger situation, in terms of assuring consumers that there remains a connection to the brand’s past. The data show that the logo chosen by consumers reflects their aesthetic responses, whereas the selected name reflects their evaluation of the brand’s offers or its presence in the market. Originality/value – The paper uses an innovative research design which gives respondents freedom to choose their preferred solution; hence, the richness of the results is enhanced. The results should guide managers in their evaluation and choices regarding post-merger branding strategies. Keywords: Brand, Brand identity signs, Brand logo, Mergers and acquisitions, Consumer preferences, Consumer behaviour, Corporate identity Paper type: Research paper